2008
DOI: 10.2165/0002018-200831120-00009
|View full text |Cite
|
Sign up to set email alerts
|

Serious Events with Infliximab in Patients with Inflammatory Bowel Disease

Abstract: Clinicians prescribing biological therapies should be aware of the development of serious events in their patients. Thorough follow-up of all patients during treatment with infliximab is warranted. If infliximab is considered in patients with IBD not responding to conventional treatment, efforts to exclude other possible underlying causes for worsening of symptoms should be made. Careful prescribing and monitoring during follow-up remains necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…30,32,34 More infections occurred in this series without any consequence for continuation of therapy. The true infection rate may possibly have been higher and underreported in the IBD charts.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…30,32,34 More infections occurred in this series without any consequence for continuation of therapy. The true infection rate may possibly have been higher and underreported in the IBD charts.…”
Section: Discussionmentioning
confidence: 61%
“…30 The absolute percentage was comparable with other longterm studies evaluating the risk of cancer during anti-TNF therapy in IBD. 32,33 It remains difficult to assess the degree of IFX involvement in pathogenesis of neoplasia in the course of IBD. Considering the pleiotropic effects of TNF, it cannot be ruled out that IFX is related to development of any neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 3) Infliximab Data on long-term infliximab safety have been derived from 37 trials [7, 9, 10, 13, 17, 13, 17-24, 27, 28, 34-38, 40, 41, 44, 48-56, 58, 67-71], including 21 on patients with CD [7, 9, 10, 13, 18-20, 22-24, 27, 28, 34-38, 40, 41, 44, 67] and 9 on UC patients [48][49][50][51][52][53][54][55][56]. Seven studies reported global safety results in IBD cohorts that included both UC and CD patients, [17,21,58,[68][69][70][71] and four pediatric series reported safety issues in patients with CD [35,36] or UC [53,54]. Four studies addressed the safety issue of infliximab use as a primary analysis [67,[69][70][71].…”
Section: Studies Reporting Pooled Results For Crohn's Disease and Ulcmentioning
confidence: 99%
“…Seven studies reported global safety results in IBD cohorts that included both UC and CD patients, [17,21,58,[68][69][70][71] and four pediatric series reported safety issues in patients with CD [35,36] or UC [53,54]. Four studies addressed the safety issue of infliximab use as a primary analysis [67,[69][70][71].…”
Section: Studies Reporting Pooled Results For Crohn's Disease and Ulcmentioning
confidence: 99%
See 1 more Smart Citation